Analysis of the intestinal microbial community and inferred functional capacities during the host response to Pneumocystis pneumonia. (25th November 2016) - Samuelson, Derrick R.; Charles, Tysheena P.; de la Rua, Nicholas M.; Taylor, Christopher M.; Blanchard, Eugene E.; Luo, Meng; Shellito, Judd E.; Welsh, David A.
ABSTRACT: Background: Pneumocystis pneumonia is a major cause of morbidity and mortality in patients infected with HIV/AIDS. In this study, we evaluated the intestinal microbial communities associated with the development of experimental Pneumocystis pneumonia, as there is growing evidence that the intestinal microbiota is critical for host defense against fungal pathogens.Methods: C57BL/6 mice were infected with live Pneumocystis murina ( P. murina ) via intratracheal inoculation and sacrificed 7 and 14 days postinfection for microbiota analysis. In addition, we evaluated the intestinal microbiota from CD4+ T cell depleted mice infected with P. murina .Results: We found that the diversity of the intestinal microbial community was significantly altered by respiratory infection with P. murina . Specifically, mice infected with P. murina had altered microbial populations, as judged by changes in diversity metrics and relative taxa abundances. We also found that CD4+ T cell depleted mice infected with P. murina exhibited significantly altered intestinal microbiota that was distinct from immunocompetent mice infected with P. murina, suggesting that loss of CD4+ T cells may also affects the intestinal microbiota in the setting of Pneumocystis pneumonia. Finally, we employed a predictive metagenomics approach to evaluate various microbial features. We found that Pneumocystis pneumonia significantly alters the intestinal microbiota's inferred functional potential for carbohydrate, energy, and xenobiotic metabolism, as well as signal transduction pathways.Conclusions: Our study provides insight into specific-microbial clades and inferred microbial functional pathways associated with Pneumocystis pneumonia. Our data also suggest a role for the gut-lung axis in host defense in the lung.